The Herbalist Game Edukasi Pengobatan Herbal Berbasis Android - Afrianto, Irawan; Furqon, Rifan Muhammad (Universitas Diponegoro, 2018)
Herbal treatment is a method of treatment using natural ingredients that are all around us. Introducing herbal medicines and treatments can be performed using educational games. The purpose of this research is to develop educational games that can teach users to be able to know the ingredients of herbs and how to process it into a drug to cure a disease. The method used in the development of this educational game is multimedia development life cycle (MDLC). The MDLC method is used to develop this educational game, starting with the concept definition stage, the design phase, followed by the collecting material stage, followed by the assembly stage, testing, and ending with the distribution stage. This educational game is a type of simulation that visualizes the form of herbal ingredients, and how to manufacture herbal medicine derived from these materials to cure a disease. Games using mobile devices have advantages that learning can be done anywhere and anytime, so the android platform is chosen as the media development of this educational game. Educational game testing is done using the alpha method to determine the functionality of the application, and beta test to the user. Alpha testing shows that every functionality in this educational game has gone well. While beta testing conducted with questionnaires shows that this educational game is enough to help users add knowledge about herbal ingredients and how to make herbal remedies through images, animation and how to play. In addition, the interface of this game is quite interesting and easy to use.